Algorithm development of liquid desiccant system - Lim, Joel Kheng Hong. (2012)
As people are more aware of the environmental issue such as global warming, liquid desiccant dehumidifier is seen as an alternate dehumidification solution as compared to air-conditioning system. Liquid desiccant dehumidifier is drawing more attention because it is more energy efficient. It is able to improve indoor air quality and achieve lower humidity. The performance of the humidifier is affected concentration of the liquid desiccant, flow rate of solution and design of the system. A control panel will be developed using LabVIEW to monitor the signal collected from the different sensors placed at different part of the system. Analyzing the results and studying the relationship between various parameters such as flow rate, temperature, concentration of desiccant solution, temperature and humidity of air, and understand how it affects each other and the dehumidification process. In this report, it will explain how temperature affects the rate of regeneration rate. It will also list the different consideration in data acquisition.